2021
DOI: 10.1101/2021.08.06.21261709
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of the COVID-19 pandemic on diagnoses of common mental health disorders in adults in Catalonia, Spain

Abstract: Objectives: To investigate how incidence trends of anxiety and depressive disorders have been affected by the COVID-19 pandemic. Design: Population-based cohort study. Setting: Observational cohort study from 2018 to 2021 using the Information System for Research in Primary Care (SIDIAP) database in Catalonia, Spain. Participants: 4,255,847 individuals aged 18 or older in SIDIAP on 1 March, 2018 with no prior history of anxiety and depressive disorders. Primary and secondary outcomes measures: Incidence of an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…[18][19][20] The impact of the pandemic on trends in diagnoses of anxiety and depression has also been studied. 21 In our descriptive analysis we found that individuals with a COVID-19 outcome were typically older and had more comorbidities than the general population. This was particularly pronounced for the most severe outcomes studied.…”
Section: Discussionmentioning
confidence: 81%
“…[18][19][20] The impact of the pandemic on trends in diagnoses of anxiety and depression has also been studied. 21 In our descriptive analysis we found that individuals with a COVID-19 outcome were typically older and had more comorbidities than the general population. This was particularly pronounced for the most severe outcomes studied.…”
Section: Discussionmentioning
confidence: 81%